More equal than others : America from Nixon to the new century - Hodgson, Godfrey (Politics and society in twentieth-century America., 2004)
During the past quarter century, free-market capitalism was recognized not merely as a successful system of wealth creation, but as the key determinant of the health of political and cultural democracy. Now, renowned British journalist and historian Godfrey Hodgson takes aim at this popular view in a book that promises to become one of the most important political histories of our time. More Equal Than Others looks back on twenty-five years of what Hodgson calls "the conservative ascendancy" in America, demonstrating how it has come to dominate American politics. Hodgson disputes the notion tha